2016
DOI: 10.1007/s00432-016-2292-3
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral pelvic lymph node dissection for Chinese patients with penile cancer: a multicenter collaboration study

Abstract: Bilateral PLND may improve survival in pN2 patients. Men with pN3 may not benefit from bilateral PLND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…All 57 patients with PLNM had inguinal LNM. As opposed to other studies where crossover was not found [9,10,12], two patients with unilateral inguinal LNM had bilateral PLNM, suggesting crossover from inguinal nodes to contralateral pelvic nodes. Lopes et al similarly documented metastasis to the pelvic nodes with no inguinal involvement [15].…”
Section: Lymph Node Mappingcontrasting
confidence: 99%
See 2 more Smart Citations
“…All 57 patients with PLNM had inguinal LNM. As opposed to other studies where crossover was not found [9,10,12], two patients with unilateral inguinal LNM had bilateral PLNM, suggesting crossover from inguinal nodes to contralateral pelvic nodes. Lopes et al similarly documented metastasis to the pelvic nodes with no inguinal involvement [15].…”
Section: Lymph Node Mappingcontrasting
confidence: 99%
“…Chipollini et al performed PLND in 198 chemonaïve patients, of which 106 (53.5%) were bilateral dissections. The median number of lymph nodes (LN) and the median number of positive LN were 13 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)) and 2 (1-4), respectively. The survival analysis revealed that patients with a lymph node yield of ≥9 LN had better 5-year disease-specific survival (DSS) (64.2% vs. 47.2%), overall survival (OS) (60.3% vs. 39.8%), and recurrencefree survival (RFS) (60.3% vs. 43.2%).…”
Section: Pelvic Lymph Node Yield Impacts Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] The main treatment for PSCC is currently a partial or radical penectomy with or without bilateral inguinal Dovepress Dovepress 2984 Zhou et al lymphadenectomy, along with radiation, chemotherapy, and targeted therapy. 1,[6][7][8][9] Some classical serum biomarkers (such as CEA, AFP, PSA, and CA-199) are clinically useful in many cancers [10][11][12] ; however, they are not suitable in penile cancer. Serum C-reactive protein (CRP) and squamous cell carcinoma antigen (SCC-Ag) were reported to be prognostic markers in PSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent contemporary series of only modified template ILND (cases from 2002 to 2011) cited a lower complication rate of 10% with only a quarter of these complications being major ( 11 ). The concern persists, however, that one must not sacrifice lymph node yield for morbidity as many studies have demonstrated that greater lymph node yield and lower lymph node density portend survival benefit ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%